SIRT1 Deacetylase Activity and the Maintenance of Protein Homeostasis in Response to Stress: An Overview - Monteiro, Jomar Patricio [UNESP]; Nogueira Cano, Maria Isabel [UNESP] (Bentham Science Publ Ltd, 2011)
The present review intends to summarize the, yet preliminary, but very important emerging data underlining the functions exerted by the nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase SIRT1 on protein homeostasis. The main focus of the discussion is the cooperation between SIRT1 and the heat shock factor 1 (HSF1) responsible for activating the transcription of molecular chaperones, the protein-protective factors that resolve damaged/misfolded and aggregated proteins generated by heat stress or metabolism. SIRT1, a mammalian ortholog of the yeast silent information regulator 2, is a stress activated protein deacetylase that contributes to life-span extension by regulating different cell survival pathways, including replicative senescence, inflammation and resistance to hypoxic and heat stress. Phosphorylation is the major mechanism controlling the level and function of SIRT1 required for normal cell cycle progression and cell survival under stress conditions. Phosphorylated SIRT1 deacetylates and coactivates different substrates, including HSF1. Deacetylated HSF1 binds to the heat shock promoter element found upstream of genes encoding molecular chaperones. Overexpression of SIRT1 in cultured cells also helps them to survive exposure to heat stress. Conversely, its down-regulation accelerates the attenuation of the heat shock response promoting the release of HSF1 from its cognate promoter element. Very recently, in a mouse model for Alzheimer's disease, SIRT1 deacetylase activity was also found activating the transcription of alpha-secretase, the enzyme responsible for inhibiting the formation of aggregates of neuronal beta-amyloid plaques. How SIRT1 activity protects cells from the deleterious effects of damaged/misfolded proteins and the implication of these findings on age-related pathologies are discussed.
Keywords: Deacetylation; heat shock factor 1 (HSF1); molecular chaperones; protein homeostasis; sirtuin; SIRT1